2017
DOI: 10.4103/1119-3077.208954
|View full text |Cite
|
Sign up to set email alerts
|

Structural echocardiographic abnormalities seen in HIV/AIDS patients are independent of cd4 count

Abstract: Echo is an important tool for detecting cardiac abnormalities in HIV/AIDS patients. There is a high prevalence of echo abnormalities among HIV patients seen in our centre. The HIV infection was associated with increased structural dimensions of cardiac chambers compared with HIV-negative controls. This however did not seem to be related to disease severity as the chamber dimensions were similar between those with CD4 count below and above 200 cells/mm3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 0 publications
3
23
1
Order By: Relevance
“…This indicates that this association depends on HIVrelated factors, rather than ART use. This is in accordance to previous studies in both highincome settings and SSA that found a higher LVM index in PLHIV compared to HIV-negative controls [9,38,39,44,45]. Both higher immune activation and increased atherosclerotic processes have been proposed as a possible cause of the increase in LVM in PLHIV, in addition to conventional risk factors like obesity and hypertension [44,46].…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…This indicates that this association depends on HIVrelated factors, rather than ART use. This is in accordance to previous studies in both highincome settings and SSA that found a higher LVM index in PLHIV compared to HIV-negative controls [9,38,39,44,45]. Both higher immune activation and increased atherosclerotic processes have been proposed as a possible cause of the increase in LVM in PLHIV, in addition to conventional risk factors like obesity and hypertension [44,46].…”
Section: Plos Onesupporting
confidence: 92%
“…Multiple studies, both in high-income countries and SSA, have reported higher rates of diastolic dysfunction in PLHIV compared to HIV-negative people [37][38][39], and this has been associated with HIV-related factors like nadir CD4 cell count [40]. Diastolic function, as evaluated with E/A ratio and LA volume, did not differ between the groups in our study following adjustment for age and sex.…”
Section: Plos Onesupporting
confidence: 39%
“…Studies from Congo and Cameroon showed prevalence of effusion of 20.4% and 46.5% respectively, showing very high prevalence in Africa (31,32). Others reported prevalence of as low as 4% to 16.6% (7,8,10,21,27,30,33,34) and in one study only two patients had pericardial effusion (35). There is a difference of the participants of the studies with some including patients with profound immunosuppression.…”
Section: Discussionmentioning
confidence: 92%
“…Neoformans and Herpes Simplex (30). Malignancies such as Lymphoma and Kaposi Sarcoma which have become less common with the widespread use of ART are other potential causes (5,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation